Analisis Framing Berita Penembakan Jurnalis AS di Ukraina pada CNNIndonesia.com dan Sindonesws.com - Gilang Aulia Paramitha; Ahmad Abdul Karim (Jurnal Ilmiah Wahana Pendidikan, 2022)
The feud between Russia and Ukraine has taken the world by storm. Reports related to the dispute between the two countries were presented in various ways by various mass media around the world, including the Indonesian mass media. One of the interesting news on the sidelines of the conflict between Russia and Ukraine is the news of the shooting of US journalists in Ukraine. The topic became a hot issue between the onslaught of war between the two countries. The purpose of this research is to look at the framing done by CNNIndonesia.com and Sindonews.com in reporting on the shooting of US journalists in Ukraine. The research method utilizes a qualitative paradigm and applies the concept of framing Pan and Kosicki. The results of the analysis of CNNIndonesia.com and Sindonesws.com chose the same issue in reporting information. But both framed the shooting of US journalists in Ukraine with different styles of expression. CNNIndonesia.com uses the concept of an inverted pyramid while SindoNews.com does not use the concept of an inverted pyramid. CNNIndonesia.com gives freedom to readers to construct the issue shooting, while Sindonews.com blames the Russian army for the shooting of the US journalist, thus defend the victim. The language used by Sindonews.com is more interesting than CNNIndonesia.com. This shows that the two media have different expressive styles in providing information to the public. The results of the analysis can be used as one of the news text teaching materials so that students can love each other between humans.